THE SHOELACE ALGORITHM IN ENGINEERING: PYTHON APPLICATIONS FOR AREA AND INERTIAL ANALYSIS - Dumka, Pankaj; Mishra, Dhananjay R. (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
The Shoelace Method is a classic mathematical formula for the determination of the area of polygons. This method is based on the vertex coordinates of a polygon and has significant applications in science and engineering. This article explores the method's extension to calculate the centroids and moments of inertia of plane shapes, which is essential for structural and mechanical analysis. By executing these calculations in Python programming, the study shows the method's practicality and flexibility for modern engineering tasks. The article introduces a Python-based structure using libraries like NumPy, Shapely, and Matplotlib for enabling efficient computational modelling and visualization. Through example problems, the versatility of the Shoelace Method in solving real-world engineering shapes is showcased.